0
$\begingroup$

I am solving a recurrence relation

$a_0 = a_1 = a_2 = 1, a_{n+3} = a_{n+2} − 2a_{n+1} − 4a_n$ for $n \ge 0$

I got a generating function for this sequence

$f(x) = \frac{2x^2+1}{4x^3+2x^2-x+1} $

Now I want to get the formula for the n-th term of this sequence. And so I wanted to use the partial fractions method but so far I was unsuccesful in finding the partial fraction. I'm probably missing something simple here.

$\endgroup$
  • $\begingroup$ $x=-1$ cancels the denominator. The other roots are complex.. $\endgroup$ – Claude Leibovici Apr 2 '16 at 8:26
0
$\begingroup$

hint:

$$4x^3 +2x^2 -x +1=(4x^2 -2x +1) (x+1) $$

$\endgroup$
  • $\begingroup$ so now I got the partial fraction of $f(x) = \frac{3}{7(x+1)} + f(x) = \frac{2x+4}{7(4x^2-2x+1)} $ How can I manipulate the second fraction with x in the numerator to get the n-th term formula? The first fraction is easy but I'm not so sure about the second one @MotylaNogaTomkaMazura $\endgroup$ – mathew7k5b Apr 2 '16 at 9:03
  • $\begingroup$ $$\frac{2x+4}{4x^2 -2x +1} =\frac{(2x+4)(2x+1)}{(2x)^3 +1} =\frac{(2x+4)(2x+1)}{1+(2x)^3 }=\frac{(2x)^2}{1+(2x)^3 } +\frac{5\cdot (2x)}{1+(2x)^3 }+$$ $$\frac{4}{1+(2x)^3 } =(2x)^2 \sum_{n=0}^{\infty} (-(2x)^3)^n+5\cdot (2x)\sum_{n=0}^{\infty} (-(2x)^3)^n +4 \sum_{n=0}^{\infty} (-(2x)^3)^n$$ $\endgroup$ – MotylaNogaTomkaMazura Apr 2 '16 at 11:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.